Cultural Sufism: A Social Construction Of Defense Heritage Of The Nation's Ancestors - Laksono, Rudi; Hendra, Afrizal; G Samudro, Eko (CV. Inara, 2025)
Cultural Sufism, as an integral part of Indonesia's culture and spirituality, not only functions as a mystical practice but also plays a significant role in the social construction related to defense. This study aims to demonstrate the relationship between Sufism and the cultural values inherited from ancestors and how cultural Sufism can become a force in preserving the nation's identity and integrity amidst the currents of globalization and modernization. Using an interdisciplinary approach, this research analyzes cultural Sufism through the lens of the social construction of reality, focusing on the Nusantara version of Sufi teachings to strengthen the collective awareness that the cultural heritage of ancestors remains strategic in the contemporary era. The study reveals that cultural Sufism functions not only as a spiritual practice but also as a form of cultural defense that unites social values, traditions, and wisdom in confronting the challenges of the times. The findings offer new insights into how cultural Sufism can serve as one of the tools of defense against threats to diversity, national integrity, and the ideals of defending the nation.